The Correlation Among COVID-19 Vaccine Acceptance, the Ability to Detect Fake News, and e-Health Literacy - Abouzar Nazari; Maede Hoseinnia; Asiyeh Pirzadeh; Arash Salahshouri (SLACK Incorporated, 2023)
Background: The coronavirus disease 2019 (COVID-19) pandemic has seen a rise in the spread of misleading and deceptive information, leading to a negative impact on the acceptance of the COVID-19 vaccine and public opinion. To address this issue, the importance of public e-Health literacy cannot be overstated. It empowers individuals to effectively utilize information technology and combat the dissemination of inaccurate narratives. Objective: This study aimed to investigate the relationship between the ability to identify disingenuous news, electronic health literacy, and the inclination to receive the COVID-19 immunization. Methods: In this descriptive-analytical cross-sectional study conducted during summer 2021 in Isfahan, Iran, 522 individuals older than age 18 years, seeking medical attention at health centers, were surveyed. The participants were selected through a meticulous multistage cluster sampling process from the pool of individuals referred to these health centers. Along with demographic information, data collection instruments included the standard e-Health literacy questionnaire and a researcher-developed questionnaire designed to identify misinformation. The collected questionnaires were entered into SPSS 24 for statistical analysis, which included the Kruskal-Wallis test, the Chi-square test, the Spearman test, and logistic regression models. Key Results: The study findings revealed a statistically significant relationship between acceptance of the COVID-19 vaccine and the ability to identify deceptive news. An increase of one unit in the score for recognizing misinformation led to a 24% and 32% reduction in vaccine hesitancy and the intention to remain unvaccinated, respectively. Furthermore, a significant correlation was found between the intention to receive the vaccine and e-Health literacy, where an increase of one unit in e-Health literacy score corresponded to a 6% decrease in the intention to remain unvaccinated. Additionally, the study found a notable association between the ability to detect false and misleading information and e-Health literacy. Each additional point in e-Health literacy was associated with a 0.33% increase in the capacity to identify fake news (Spearman's Rho = 0.333, p < .001). Conclusion: The study outcomes demonstrate a positive correlation between the COVID-19 vaccine acceptance, the ability to identify counterfeit news, and proficiency in electronic health literacy. These findings provide a strong foundation for policymakers and health care practitioners to develop and implement strategies that counter the dissemination of spurious and deceitful information related to COVID-19 and COVID-19 immunization. [HLRP: Health Literacy Research and Practice. 2023;7(3):e130-e138.] Plain Language Summary: We investigated the relationship between the ability to detect fake news and e-health literacy, with acceptance of a COVID-19 vaccine in Isfahan. The results demonstrated that acceptance of the COVID-19 vaccine is associated with a high level of ability to detect fake news and high level of e-Health literacy in individuals. Also, the high level of e-health literacy increases the ability to detection of fake news.